University and place branding: The case of universities located in ECC (European Capital of Culture) cities (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2015)
In the globalising landscape of higher education more and more universities are going international. These universities are facing growing competition, especially in enrolling international students. International competition forces them to use marketing and especially branding activity. University branding requires that the higher education institutions clearly define their differentiating features. One of the most important differentiating features is the place where the institution is located. University and place branding should work together to help the potential students in their decisions to choose the place of their study. The ECC (European Capital of Culture) program which started in 1985 has helped many cities to identify their values and to develop their place branding activities. The study examines how the European Capital of Culture designation of the city helped the marketing activities of the universities located in these cities. The study attempts to explore to what extent universities located in ECCs used this special feature of their cities in their international marketing communication. The paper also attempts to analyse the effects the European Capital of Culture title could have on the international student enrolment activity of the concerned universities.